Method for producing toner for developing electrostatic images, and toner for developing electrostatic images

JP7651951B2Active Publication Date: 2025-03-27FUJIFILM BUSINESS INNOVATION CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021086314
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-21
Publication Date
2025-03-27
Estimated Expiration
2041-05-21

AI Technical Summary

Benefits of technology

【0007】 <1>、<2>、<9>又は<10>に係る発明によれば、非晶性樹脂を含むトナー粒子と添加剤粒子とを混合する混合工程を含み、前記混合工程に使用される混合装置が、撹拌槽、撹拌羽根、及び、前記撹拌槽を冷却可能であるジャケットを有し、前記混合工程における前記混合装置内温度Tiが、前記トナー粒子の表面近傍に含まれる前記非晶性樹脂のガラス転移温度Tgに対し、Tg-50℃未満若しくはTg以上であるか、又は、下記式2若しくは式3を満たさない場合に比べ、転写性、及び、画像ムラ抑制性に優れる静電荷像現像用トナーの製造方法が提供される。 <3>に係る発明によれば、前記混合工程における前記ジャケットの通水により冷却を開始する前記混合装置内温度設定値が、前記非晶性樹脂のガラス転移温度Tg-30℃未満又は前記非晶性樹脂のガラス転移温度Tg-5℃超である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <4>に係る発明によれば、前記混合工程における前記撹拌羽根の回転数が、20m/sec未満又は80m/sec超である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <5>に係る発明によれば、前記混合工程における混合終了時の装置内温度Teが、前記非晶性樹脂のガラス転移温度Tg-25℃未満又は前記非晶性樹脂のガラス転移温度Tg-10℃超である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <6>に係る発明によれば、前記添加剤粒子が、1種のみを含む場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <7>に係る発明によれば、前記大径添加剤粒子の算術平均粒径が、100nm未満である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <8>に係る発明によれば、前記混合工程で混合されたトナーにおいて、前記トナー粒子に付着していない前記添加剤粒子の割合を表す遊離率が60%未満であるか、又は、超音波脱離処理後のトナーに付着している添加剤の割合を表す強付着率が、前記大径外添剤は30%未満であるか、若しくは、前記小径外添剤は80%未満である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <11>に係る発明によれば、前記混合工程の混合時間が、5分間未満又は30分間超である場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <12>に係る発明によれば、前記混合工程において混合終了時の装置内温度をTe、混合開始後2分から混合終了までの装置内の平均温度をTaとし、連続して2回以上混合工程を実施した際の1回目のTeであるTe1とn回目のTeであるTen及び1回目のTaであるTa1とn回目のTaであるTanのいずれか1つが、|Ten-Te1|≦10℃、かつ、|Tan-Ta1|≦10℃を満たさない場合に比べ、転写性、及び、画像ムラ抑制性により優れる静電荷像現像用トナーの製造方法が提供される。 <13>に係る発明によれば、トナーの製造方法において、非晶性樹脂を含むトナー粒子と添加剤粒子とを混合する混合工程を含み、撹拌槽、撹拌羽根、及び、前記撹拌槽を冷却可能であるジャケットを有し、前記混合工程における前記混合装置内温度Tiが、前記トナー粒子の表面近傍に含まれる前記非晶性樹脂のガラス転移温度Tgに対し、Tg-50℃未満若しくはTg以上であるか、又は、下記式2若しくは式3を満たさない場合に比べ、転写性、及び、画像ムラ抑制性に優れる静電荷像現像用トナーが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651951000003
    Figure 0007651951000003
  • Figure 0007651951000004
    Figure 0007651951000004
  • Figure 0007651951000005
    Figure 0007651951000005
Patent Text Reader

Abstract

To provide a method for manufacturing a toner for electrostatic charge image development, which is excellent in transferability and image unevenness suppression.SOLUTION: A method for manufacturing a toner for electrostatic charge image development includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, wherein a mixing device used in the mixing step has an agitation vessel, an agitation blade and a jacket capable of cooling the agitation vessel and satisfies the following condition (1) and condition (2). Condition (1): temperature Ti in the mixing device in the mixing step, with respect to a glass transition temperature Tg of the amorphous resin contained in the vicinity of the surface of the toner particles, satisfies: Tg-50°C≤Ti<Tg (Formula 1). Condition (2): 0.08≤(Pm-P0) / w≤0.50 (Formula 2) is satisfied. In the Formula 2, Pm represents average power (kW) of a motor for driving the agitation blade of the mixing device; P0 represents empty power (kW) of the motor; and w represents a total mass (kg) of the toner particles and the additive particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a toner for developing electrostatic images, and a toner for developing electrostatic images. [Background technology]

[0002] Methods for visualizing image information, such as electrophotography, are currently used in various fields. In electrophotography, an electrostatic image is formed as image information on the surface of an image carrier by charging and forming an electrostatic image. Then, a toner image is formed on the surface of the image carrier by a developer containing a toner, and the toner image is transferred to a recording medium, and then fixed to the recording medium. Through these steps, the image information is visualized as an image.

[0003] For example, Patent Document 1 discloses a method for producing a toner for electrophotography, which includes a step of (a) mixing a powder containing 100 parts by weight of base colored particles containing a binder resin and a colorant, and 4.0 to 7.0 parts by weight of large-particle silica having a volume median particle size of 30 to 100 nm, using a mixer having a mixing blade, setting the tip peripheral speed of the mixing blade in the range of 40 to 80 m / sec and the amount of power energy input per unit weight of the powder in the range of 0.01 to 0.05 kWh / kg, and (b) raising the temperature of the powder to a temperature higher than the glass transition temperature (Tg) of the base colored particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-224159 A Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a method for manufacturing an electrostatic charge image developing toner, which includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, the mixing device used in the mixing step having a stirring tank with a jacket and stirring blades, and having a temperature control mechanism capable of passing cooling water through the jacket, and the temperature Ti in the mixing device in the mixing step being less than Tg - 50°C or not less than Tg with respect to the glass transition temperature Tg of the amorphous resin contained near the surface of the toner particles, or being excellent in transferability and image unevenness suppression as compared with the case where the following formula 2 or formula 3 is not satisfied.

Means for Solving the Problems

[0006] The means for solving the above problems include the following aspects. <1> A method for manufacturing an electrostatic charge image developing toner, which includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, the mixing device used in the mixing step having a stirring tank, stirring blades, and a jacket capable of cooling the stirring tank, and satisfying the following conditions (1) and (2). Condition (1): The temperature Ti in the mixing device in the mixing step satisfies Tg - 50°C ≤ Ti < Tg (Formula 1) with respect to the glass transition temperature Tg of the amorphous resin contained near the surface of the toner particles. Condition (2): 0.08 ≤ (Pm - P0) / w ≤ 0.50 (Formula 2) is satisfied. In Formula 2, Pm represents the motor average power (kW) of the mixing device in the mixing step, P0 represents the no-load power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles in the mixing device. <2> A method for manufacturing an electrostatic charge image developing toner, which includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, the mixing device used in the mixing step having a stirring tank, stirring blades, and a jacket capable of cooling the stirring tank, and satisfying the following conditions (1) and (3). Condition (1): The temperature Ti in the mixing device in the mixing step satisfies Tg - 50°C ≤ Ti < Tg (Formula 1) with respect to the glass transition temperature Tg of the amorphous resin contained near the surface of the toner particles. Condition (3): 40≦(Pm-P0)·t / w≦300 (Equation 3) is satisfied. In formula 3, t represents the mixing time (sec) in the mixing process, Pm represents the average motor power (kW) of the mixing device in the mixing process, P0 represents the air power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles in the mixing device. <3> The temperature setting value in the mixing device at which cooling is started by passing water through the jacket in the mixing step is equal to or higher than the glass transition temperature (Tg) of the amorphous resin −30° C. and equal to or lower than the glass transition temperature (Tg) of the amorphous resin −5° C. <1> or <2> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <4> The rotation speed of the stirring blade in the mixing step is 20 m / sec or more and 80 m / sec or less. <1> ~ <3> 13. A method for producing the toner for developing electrostatic images according to claim 12. <5> The temperature Te inside the apparatus at the end of the mixing step is equal to or higher than the glass transition temperature Tg of the amorphous resin −25° C. and equal to or lower than the glass transition temperature Tg of the amorphous resin −10° C. <1> ~ <4> 13. A method for producing the toner for developing electrostatic images according to claim 12. <6> The additive particles include one or more types of large additive particles having an arithmetic mean particle size of 60 nm or more, and two or more types of small additive particles having an arithmetic mean particle size of less than 60 nm. <1> ~ <5> 13. A method for producing the toner for developing electrostatic images according to claim 12. <7> The large-diameter additive particles have an arithmetic mean particle size of 100 nm or more. <6> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <8> In the toner mixed in the mixing step, a free ratio representing a ratio of the additive particles not adhering to the toner particles is 60% or less, and a strong adhesion ratio representing a ratio of the additive particles adhering to the toner after ultrasonic desorption treatment is 30% or less for the large-diameter external additive and 80% or less for the small-diameter external additive. <6> or <7> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <9> The additive particles include inorganic oxide particles. <1> ~ <8> 13. A method for producing the toner for developing electrostatic images according to claim 12. <10> The inorganic oxide particles include large-diameter inorganic oxide particles having an arithmetic mean particle size of 60 nm or more and small-diameter inorganic oxide particles having an arithmetic mean particle size of less than 50 nm. <9> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <11> The mixing time of the mixing step is 5 minutes or more and 30 minutes or less. <1> ~ <10> 13. A method for producing the toner for developing electrostatic images according to claim 12. <12> In the mixing step, the temperature inside the device at the end of mixing is Te, and the average temperature inside the device from 2 minutes after the start of mixing to the end of mixing is Ta. When the mixing step is performed two or more times in succession, Te1, which is the first Te, Ten, which is the nth Te, and Ta1, which is the first Ta, and Tan, which is the nth Ta, always satisfy |Ten-Te1|≦10°C and |Tan-Ta1|≦10°C. <1> ~ <11> 2. The method for producing a toner for developing an electrostatic image according to claim 1, wherein |Ten-Te1| and |Tan-Ta1| represent absolute values ​​of Ten-Te1 and Tan-Ta1, respectively. <13> <1> ~ <12> 13. A toner for developing electrostatic images, which is produced by the method for producing a toner for developing electrostatic images according to any one of claims 1 to 12. Effect of the Invention

[0007] <1> , <2> , <9> or <10> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which includes a mixing step of mixing toner particles containing an amorphous resin with additive particles, wherein a mixing device used in the mixing step has a stirring tank, a stirring blade, and a jacket capable of cooling the stirring tank, and the temperature Ti inside the mixing device in the mixing step is lower than Tg-50°C or higher than Tg, where Tg is the glass transition temperature of the amorphous resin contained in the vicinity of the surfaces of the toner particles, or the toner has excellent transferability and suppression of image unevenness compared to a case where the following formula 2 or formula 3 is not satisfied: <3> According to the invention pertaining to the above, there is provided a method for producing a toner for developing electrostatic images, which is superior in transferability and suppression of image unevenness compared to a case in which the set value of the temperature inside the mixing device, at which cooling is started by passing water through the jacket in the mixing step, is lower than the glass transition temperature Tg of the amorphous resin -30°C or higher than the glass transition temperature Tg of the amorphous resin -5°C. <4> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which has better transferability and suppression of image unevenness than when the rotation speed of the stirring blade in the mixing process is less than 20 m / sec or more than 80 m / sec. <5> According to the invention relating to the above, there is provided a method for producing a toner for developing electrostatic images, which is superior in transferability and suppression of image unevenness compared to a case in which the temperature inside the apparatus Te at the end of the mixing step is lower than the glass transition temperature Tg of the amorphous resin - 25°C or higher than the glass transition temperature Tg of the amorphous resin - 10°C. <6> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which is more excellent in transferability and suppression of image unevenness, as compared with a case in which only one type of additive particle is contained. <7> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which is superior in transferability and suppression of image unevenness compared to a case in which the arithmetic mean particle size of the large-diameter additive particles is less than 100 nm. <8> According to the invention, there is provided a method for producing a toner for developing electrostatic images, which has better transferability and suppression of image unevenness than a toner mixed in the mixing step, in which the free ratio, which represents the ratio of the additive particles not adhering to the toner particles, is less than 60%, or the strong adhesion ratio, which represents the ratio of the additive particles adhering to the toner after ultrasonic desorption treatment, is less than 30% for the large-diameter external additives or less than 80% for the small-diameter external additives. <11> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which has better transferability and suppression of image unevenness than when the mixing time in the mixing step is less than 5 minutes or more than 30 minutes. <12> According to the invention, the temperature inside the device at the end of the mixing step is Te, and the average temperature inside the device from 2 minutes after the start of mixing to the end of mixing is Ta, and when the mixing step is performed two or more times in succession, any one of Te1, the Te of the first time, Ten, the Te of the nth time, and Ta1, the Ta of the first time, and Tan, the Ta of the nth time, does not satisfy |Ten-Te1|≦10°C and |Tan-Ta1|≦10°C, a method for producing a toner for developing electrostatic images is provided, which has superior transferability and suppression of image unevenness compared to a case where |Ten-Te1|≦10°C and |Tan-Ta1|≦10°C are not satisfied. <13> According to the invention, there is provided a toner for developing electrostatic images, which includes a mixing step of mixing toner particles containing an amorphous resin with additive particles, the toner manufacturing method including a mixing tank, a mixing blade, and a jacket capable of cooling the mixing tank, and the temperature inside the mixing device in the mixing step is lower than Tg-50°C or higher than Tg, where Tg is the glass transition temperature of the amorphous resin contained in the vicinity of the surfaces of the toner particles, or the toner does not satisfy the following formula 2 or formula 3, and which has excellent transferability and suppression of image unevenness. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a schematic diagram illustrating an example of a mixing device that can be suitably used in the method for producing a toner for developing an electrostatic image according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of an agitating blade in a mixer used in the method for producing a toner for developing an electrostatic image according to the present embodiment. [Diagram 3] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 4] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Diagram 5] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 6]FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 7] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 8] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 9] FIG. 4 is a schematic diagram illustrating another example of the stirring blade in the mixer used in the method for producing the toner for developing electrostatic images according to the present embodiment. [Figure 10] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Figure 11] FIG. 2 is a schematic diagram illustrating an example of a process cartridge according to the present embodiment. [Figure 12] FIG. 2 is a schematic diagram showing an example of an additive supplying device suitably used in the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described in detail. In addition, in numerical ranges described in stages, the upper limit or lower limit value described in a certain numerical range may be replaced with the upper limit or lower limit value of another numerical range described in stages. In addition, in a numerical range, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples. When a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. The term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0010] (Method of manufacturing toner for developing electrostatic images) The first embodiment of the method for manufacturing an electrostatic charge image developing toner according to the present embodiment includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, and has a stirring tank, stirring blades, and a jacket capable of cooling the stirring tank, and is a method for manufacturing an electrostatic charge image developing toner that satisfies the following conditions (1) and (2). Condition (1): In the mixing step, the temperature Ti inside the mixing device satisfies Tg - 50°C ≤ Ti < Tg (Formula 1), where Tg is the glass transition temperature of the amorphous resin contained near the surface of the toner particles. Condition (2): 0.08 ≤ (Pm - P0) / w ≤ 0.50 (Formula 2) is satisfied. In Formula 2, Pm represents the average power (kW) of the motor that drives the stirring blades of the mixing device in the mixing step, P0 represents the idling power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles inside the mixing device.

[0011] The second embodiment of the method for manufacturing an electrostatic charge image developing toner according to the present embodiment includes a mixing step of mixing toner particles containing an amorphous resin and additive particles, and the mixing device used in the mixing step has a stirring tank with a jacket and stirring blades, and satisfies the following conditions (1) and (3). Condition (1): In the mixing step, the temperature Ti inside the mixing device satisfies Tg - 50°C ≤ Ti < Tg (Formula 1), where Tg is the glass transition temperature of the amorphous resin contained near the surface of the toner particles. Condition (3): 40 ≤ (Pm - P0)·t / w ≤ 300 (Formula 3) is satisfied. In Formula 3, t represents the mixing time (sec) in the mixing step, Pm represents the average power (kW) of the motor that drives the stirring blades of the mixing device in the mixing step, P0 represents the idling power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles inside the mixing device.

[0012] In this specification, unless otherwise specified, when the term "the method for producing the toner for developing electrostatic images according to the present embodiment" is used, it refers to both the first embodiment and the second embodiment. Furthermore, unless otherwise specified, when the term "mixing device" is used, it refers to all of the mixing devices in the first embodiment and the second embodiment. In this embodiment, the vicinity of the surface of the toner particle refers to a portion up to a depth of 200 nm from the surface of the toner particle. The electrostatic image developing toner according to this embodiment is a toner produced by the method for producing the electrostatic image developing toner according to this embodiment.

[0013] In recent years, image formation by electrophotography is required to achieve both high image quality and high reliability. Toners with small particle size and narrow particle size distribution have been developed by wet manufacturing as a method to simultaneously achieve high image quality and high reliability. However, the toner particles obtained by the wet manufacturing method alone do not meet the requirements for a developer in terms of various properties such as transferability, charging properties, and fluidity. Therefore, in order to improve these, inorganic oxide particles and the like have been mixed as external additives. The adhesion state of these external additive particles to the toner particle surface has a significant effect not only on the chargeability of the toner particles but also on the image quality. For example, if the adhesion force between the external additive particles and the toner particles is too weak (there is a lot of free components), a relatively high powder fluidity is obtained, but the charge amount and charge amount distribution of the toner deteriorate due to the adhesion of the external additive particles to the carrier, causing uneven development. Conversely, if the adhesion force with the toner particles is too strong, the transfer efficiency is reduced due to the deterioration of the fluidity of the toner particles, and the charge amount distribution is widened due to the external additive being buried in the toner. Therefore, the adhesion state of the external additive particles to the toner particle surface is optimized in the toner manufacturing process. As a method for adhering external additive particles to the toner particle surface well, a method of mixing at a temperature higher than the glass transition temperature of the toner has been proposed (see, for example, Patent Document 1). However, when mixing at a temperature higher than the glass transition temperature of the toner, external additive particles with an average particle size of 60 nm or more, which have relatively weak adhesion, can obtain a moderate adhesion, but the adhesion state of additive particles with an average particle size of less than 60 nm, which have relatively strong adhesion, becomes excessive, the external additive is buried in the toner, the charge amount distribution spreads, and image unevenness occurs.

[0014] In the manufacturing method of the toner for developing electrostatic images according to the present embodiment, it is presumed that by satisfying the above condition (1) and the above condition (2) or the above condition (3), the adhesion strength (uniform dispersibility) of the additive particles can be controlled within a good range by adjusting the temperature and power or workload in the mixing device, and a toner for developing electrostatic images having excellent transferability and suppression of image unevenness can be obtained. Furthermore, when the additive particles contain large-diameter additive particles and small-diameter additive particles, image unevenness is more likely to occur. However, even in such a case, the method for producing the toner for developing electrostatic images according to the present embodiment can provide a toner for developing electrostatic images that is excellent in transferability and suppression of image unevenness.

[0015] Each step will be described in detail below.

[0016] <Mixing process> A first embodiment of the method for producing a toner for developing an electrostatic image according to the present embodiment includes a mixing step of mixing toner particles (also simply referred to as "toner particles") containing an amorphous resin with additive particles, and a mixing device used in the mixing step includes a stirring tank having a jacket and a stirring blade, and also includes a temperature control mechanism capable of passing cooling water through the jacket, and satisfies the above conditions (1) and (2). A second embodiment of the method for producing a toner for developing an electrostatic image according to the present embodiment includes a mixing step of mixing toner particles containing an amorphous resin with additive particles, and a mixing device used in the mixing step has a stirring tank, a stirring blade, and a jacket capable of cooling the stirring tank, and satisfies the above conditions (1) and (3).

[0017] - Condition (1)- The method for manufacturing a toner for developing an electrostatic charge image according to this embodiment satisfies the following condition (1). Condition (1): In the mixing step, the temperature Ti inside the mixing device satisfies Tg - 50°C ≤ Ti < Tg (Equation 1), where Tg is the glass transition temperature of the amorphous resin contained near the surface of the toner particles. In the method for manufacturing a toner for developing an electrostatic charge image according to this embodiment, from the viewpoints of transferability and image unevenness suppression, Ti is preferably Tg - 40°C or higher and Tg - 5°C or lower, and more preferably Tg - 30°C or higher and Tg - 10°C or lower. Also, the temperature Ti inside the mixing device in the mixing step is preferably the temperature inside the stirring tank. When there are two or more kinds of amorphous resins contained near the surface of the toner particles, Tg is the glass transition temperature of the amorphous resin having the highest content near the surface.

[0018] - Condition (2)- The first embodiment of the method for manufacturing a toner for developing an electrostatic charge image according to this embodiment satisfies the following condition (2). Condition (2): 0.08 ≤ (Pm - P0) / w ≤ 0.50 (Equation 2) is satisfied. In Equation 2, Pm represents the average power (kW) of the motor that drives the stirring blades of the mixing device in the mixing step, P0 represents the no-load power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles inside the mixing device. Also, from the viewpoints of transferability and image unevenness suppression, it is preferable that the second embodiment of the method for manufacturing a toner for developing an electrostatic charge image according to this embodiment satisfies the above condition (2).

[0019] The method for manufacturing a toner for developing an electrostatic charge image according to this embodiment more preferably satisfies the following formula (2-1) and particularly preferably satisfies the following formula (2-2) from the viewpoints of transferability and image unevenness suppression. 0.10 ≤ (Pm - P0) / w ≤ 0.40 (Equation 2-1) 0.15≦(Pm-P0) / w≦0.35 (Formula 2-2)

[0020] -Condition (3)- The second embodiment of the method for producing a toner for developing an electrostatic image according to the present embodiment satisfies the following condition (3). Condition (3): 40≦(Pm-P0)·t / w≦300 (Equation 3) is satisfied. In formula 3, t represents the mixing time (sec) in the mixing process, Pm represents the average power (kW) of the motor driving the stirring blade of the mixing device in the mixing process, P0 represents the air power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles in the mixing device. In addition, the first embodiment of the method for producing the toner for developing electrostatic images according to the present embodiment preferably satisfies the above condition (3) from the viewpoints of transferability and suppression of image unevenness.

[0021] In the method for producing the toner for developing electrostatic images according to the present embodiment, it is more preferable to satisfy the following formula (3-1), and it is particularly preferable to satisfy the following formula (3-2), from the viewpoints of transferability and suppression of image unevenness. 60≦(Pm-P0)·t / w≦240 (Formula 3-1) 100≦(Pm-P0)·t / w≦200 (Formula 3-2)

[0022] The mixing device used in the mixing step has a stirring tank with a jacket and a stirring blade, and also has a temperature control mechanism capable of passing cooling water through the jacket. The mixing device is not particularly limited as long as it is a device equipped with a stirring tank, stirring blades, and a jacket capable of cooling the stirring tank, and any known mixing device can be used.

[0023] A suitable example of the mixing device is the mixing device shown in FIG. A mixing device 400 shown in FIG. 1 includes a stirring vessel 411, a stirring blade including an upper blade 406 and a lower blade 407, and a jacket (not shown) capable of cooling the stirring vessel 411. The raw powder of toner particles and additive particles is fed from the top of the mixing tank 411 and batch-processed. The inside of the mixing tank 411 is open via a ventilation filter 403 so that the pressure inside is always atmospheric. The stirring blade, which is composed of upper blade 406 and lower blade 407, is rotated by using a motor 405 as power. The material to be treated, which has flowed upward due to the rotation of the lower blade 407, is strongly sheared by the upper blade 406. The centrifugal force caused by these rotational movements causes the material to be biased toward the wall of the mixing tank 411. The material is pushed back toward the center of the mixing tank 411 by the deflector 404, the angle of which can be adjusted. This series of flows creates a circulating flow, and a mixture with excellent uniformity is obtained. The inside of the stirring tank 411 is cooled by passing cooling water such as 5° C. cold water through a jacket (not shown). The cooling water enters from a cooling water inlet 401 and is discharged from a cooling water outlet 402. The temperature inside the stirring tank 411 can be measured by a temperature sensor 410 such as a thermocouple or a resistance temperature detector. The jacket may pass not only cooling water but also hot water or the like. The jacket may further include a temperature control mechanism linked to the temperature sensor 410. The temperature control by the temperature control mechanism may be performed manually or automatically.

[0024] The shape and material of the stirring vessel used in this embodiment are not particularly limited, and known materials may be used, but from the viewpoint of the cooling efficiency of the jacket, it is preferable that the stirring vessel be made of metal.

[0025] The shape and material of the stirring blade used in this embodiment are not particularly limited, and known blades may be used. Among them, from the viewpoints of transferability and suppression of image unevenness, a suitable stirring blade is an stirring blade having an upper blade and a lower blade in combination. The shapes and materials of the upper and lower blades are not particularly limited, and known shapes and materials may be used, and may be appropriately combined depending on the application. Preferred upper and lower blades are those having the shapes shown in Figs. More preferably, the upper blade has a shape shown in FIG. 2 or FIGS. 6 to 9, and more preferably, the lower blade has a shape shown in FIGS. The lower blade S0 (lower) shown in FIG. 4 is a lower blade with very strong uplifting power. The upper blade Z0 (top) shown in Figure 6 creates a vigorous motion and is suitable for processing relatively large amounts or for kneading viscous slurry or mochi-like materials. The upper blade CK (top) shown in Figure 7 has the effect of pressing the material to be treated against the wall of the mixing vessel, and since the blades are in two stages and located at a high position, it is excellent for large-volume processing. The upper blade P0 (top) shown in FIG. 8 is a blade that is easy to adjust the particle size at low speeds because the blade rises at the part where the peripheral speed is the fastest. The upper blade Y2 (top) shown in FIG. 9 has a fin provided between the first and second stages, and the ring-shaped blade eliminates up and down pulsation, allowing for well-balanced stirring. Among these, a stirring blade that combines the upper blade Z0 (top) shown in FIG. 6 and the lower blade B0 (bottom) shown in FIG. 5 is particularly preferred because it is easy to control the liberation rate of both large and small diameter additive particles.

[0026] The rotation speed of the stirring blade in the mixing step is not particularly limited, but from the viewpoints of transferability and suppression of image unevenness, it is preferably 5 m / sec or more and 100 m / sec or less, more preferably 10 m / sec or more and 90 m / sec or less, and particularly preferably 20 m / sec or more and 80 m / sec or less.

[0027] The inside of the stirring tank is cooled by passing cooling water, such as 5° C. cold water, through the jacket. The temperature control in the stirring tank may be performed, for example, by stopping water flow through the jacket at the start of a batch in the mixing process, constantly monitoring the temperature in the stirring tank with a thermocouple or a resistance temperature detector, starting water flow through the jacket when the temperature rise in the tank due to heat of mixing or the like from the start of mixing exceeds a temperature set in the recipe conditions, and stopping water flow when the batch ends or the temperature drops below the temperature set in the recipe conditions. It is also preferable to control the temperature in the stirring tank according to recipe conditions set for each product type from a process control computer at a higher level of control. By using the temperature control method, the final temperature of each batch can be controlled within a certain range, and the temperature profile in the tank for successive batches can be stabilized. Each batch in the mixing process is specified by the mixing time. In addition, the temperature of the oil used for shaft cooling is stabilized with cooling water, thereby enabling stable equipment mixing. The cooling water flow through the jacket can be controlled, for example, by an automatic valve installed in the equipment piping connected to the cooling water inlet. The automatic valve is opened to start the water flow through the jacket, and closed to stop the water flow through the jacket. The automatic control device for the mixing step may monitor the temperature in the stirring tank with a thermocouple or a resistance temperature detector, and open the automatic valve installed in the equipment piping at the temperature set by the prescription conditions. The automatic valve may be operated at any timing by switching the automatic control device to manual mode.

[0028] The set value of the temperature inside the mixing device at which cooling is started by passing water through the jacket in the mixing step is, from the viewpoints of transferability and suppression of image unevenness, preferably not less than the glass transition temperature (Tg) of the amorphous resin -30°C and not more than the glass transition temperature (Tg) of the amorphous resin -5°C, and more preferably not less than the glass transition temperature (Tg) of the amorphous resin -20°C and not more than the glass transition temperature (Tg) of the amorphous resin -5°C.

[0029] In the mixing step, an additive feeder can be used to efficiently weigh and feed a plurality of additive particles to the stirring device. A suitable additive feeder is, for example, the device shown in FIG. 12. 12 includes, for example, a weighing hopper 502 capable of weighing additive particles and a conveying mechanism 504 such as wheels capable of conveying the hopper, and when weighing and feeding a plurality of additive particles into a mixing device 600, the additive feeding device moves to weighing and discharging means 512a, 512b, 512c of extruders 506a, 506b, 506c of the additive particles, and the extruded additive can be weighed in a predetermined amount by the weighing hopper 502. In addition, the additive feeding device 500 may weigh a plurality of additive particles and then feed the weighed additive into a mixing device 600 that mixes the toner particles and the additive particles. It is also possible to set prescriptions such as movement of the additive dosing device 500 to each of the metering and discharging means 512a, 512b, and 512c, setting of a predetermined amount of metering, and number of operations, and the prescription settings can also be set in the additive dosing device 500 from a process control computer (not shown). In addition, the additive dosing device 500 can select an independent operation of the additive dosing device or an operation linked to another process.

[0030] From the viewpoints of transferability and suppression of image unevenness, the temperature Te inside the apparatus at the end of mixing in the mixing step is preferably not less than the glass transition temperature Tg of the amorphous resin -30°C and not more than the glass transition temperature Tg of the amorphous resin -5°C, and more preferably not less than the glass transition temperature Tg of the amorphous resin -25°C and not more than the glass transition temperature Tg of the amorphous resin -10°C.

[0031] From the viewpoints of transferability and suppression of image unevenness, the mixing time in the mixing step is preferably from 1 minute to 60 minutes, more preferably from 2 minutes to 40 minutes, and particularly preferably from 5 minutes to 30 minutes.

[0032] From the viewpoint of transferability and suppression of image unevenness, the temperature inside the apparatus at the end of mixing in the mixing step is Te, and the average temperature inside the apparatus from 2 minutes after mixing begins to the end of mixing is Ta. When the mixing step is performed two or more times in succession, it is preferable that Te1, the first Te, Ten, the nth Te, and Ta1, the first Ta, and Tan, the nth Ta, always satisfy |Ten-Te1|≦10°C and |Tan-Ta1|≦10°C, it is more preferable that |Ten-Te1|≦8°C and |Tan-Ta1|≦8°C, and it is particularly preferable that |Ten-Te1|≦5°C and |Tan-Ta1|≦5°C.

[0033] Preferred embodiments of each component, such as a binder resin, a release agent, and a colorant, contained in the toner particles containing an amorphous resin in the mixing step will be described below.

[0034] The additive particles in the mixing step are preferably external additives for the toner. The additive particles include, for example, inorganic particles and organic particles. The inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0035] The surface of the inorganic particles is preferably subjected to a hydrophobic treatment. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is preferably, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0036] Examples of additive particles include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, fatty acid metal salt particles such as zinc stearate, and fluorine-based polymer particles), and the like.

[0037] Among these, from the viewpoint of further exerting the effects of this embodiment, the additive particles preferably include one or more types of large-diameter additive particles having an arithmetic mean particle size of 60 nm or more and one or more types of small-diameter additive particles having an arithmetic mean particle size of less than 60 nm, more preferably one or more types of large-diameter additive particles having an arithmetic mean particle size of 60 nm or more and two or more types of small-diameter additive particles having an arithmetic mean particle size of less than 60 nm, and particularly preferably one or two types of large-diameter additive particles having an arithmetic mean particle size of 60 nm or more and two or three types of small-diameter additive particles having an arithmetic mean particle size of less than 60 nm. The arithmetic mean particle size of the large additive particles is preferably 70 nm or more, more preferably 85 nm or more, and particularly preferably 100 nm or more, from the viewpoints of transferability and suppression of image unevenness. In addition, the upper limit of the arithmetic mean particle size of the large-diameter additive particles is preferably 8 μm or less, more preferably 5.0 μm or less, even more preferably 300 nm or less, and particularly preferably 200 nm or less, from the viewpoints of transferability and suppression of image unevenness. Furthermore, from the viewpoints of transferability and suppression of image unevenness, the arithmetic mean particle size of the small diameter additive particles is preferably 5 nm or more and less than 60 nm, more preferably 5 nm or more and 40 nm or less, and particularly preferably 5 nm or more and 30 nm or less.

[0038] In the present embodiment, the arithmetic mean particle size of additive particles is measured by observing the particles with a scanning electron microscope (S-4100 manufactured by Hitachi, Ltd.) and taking images. The taken images are imported into image processing and analysis software WinRoof (manufactured by Mitani Shoji Co., Ltd.), and the area of ​​each particle is determined by image analysis, and the equivalent circle diameter (nm) is determined from the area. The arithmetic mean of the equivalent circle diameters of 100 or more particles is calculated to obtain the arithmetic mean particle size.

[0039] In addition, from the viewpoint of further exerting the effects of this embodiment, the additive particles preferably contain inorganic oxide particles, preferably containing large-sized inorganic oxide particles having an arithmetic mean particle size of 60 nm or more and small-sized inorganic oxide particles having an arithmetic mean particle size of less than 60 nm, more preferably containing one or more types of large-sized inorganic oxide particles having an arithmetic mean particle size of 60 nm or more and two or more types of small-sized inorganic oxide particles having an arithmetic mean particle size of less than 60 nm, and particularly preferably containing one or two types of large-sized inorganic oxide particles having an arithmetic mean particle size of 60 nm or more and two or three types of small-sized inorganic oxide particles having an arithmetic mean particle size of less than 60 nm.

[0040] Examples of inorganic oxide particles include silica particles, titania particles, silica-titania composite particles, alumina particles, etc. Among them, at least one type of particle selected from the group consisting of silica particles, titania particles, and silica-titania composite particles is preferred, and silica particles are particularly preferred.

[0041] Favorable examples of the additive particles include fatty acid metal salt particles. Examples of fatty acid metal salt particles include particles of salts of fatty acids (e.g., fatty acids such as stearic acid, 12-hydroxystearic acid, behenic acid, montanic acid, lauric acid, and other organic acids) and metals (e.g., calcium, zinc, magnesium, aluminum, and other metals (Na, Li, etc.)). Specific examples of fatty acid metal salt particles include particles of zinc stearate, magnesium stearate, calcium stearate, iron stearate, copper stearate, magnesium palmitate, calcium palmitate, manganese oleate, lead oleate, zinc laurate, zinc palmitate, and the like. Of these fatty acid metal salt particles, zinc stearate particles are preferred from the viewpoints of lubricity, hydrophobicity, wettability, and the like.

[0042] The amount of additive particles added is not particularly limited, but from the viewpoint of transferability and suppression of image unevenness, it is preferably from 0.01% by mass to 10% by mass, and more preferably from 0.01% by mass to 8% by mass, based on the total mass of the toner particles. In addition, the amount of the large-diameter additive particles added is preferably from 0.5% by mass to 10% by mass, more preferably from 1.0% by mass to 8% by mass, and even more preferably from 1.5% by mass to 6% by mass, based on the total mass of the toner particles, from the viewpoints of transferability and suppression of image unevenness. The amount of small diameter additive particles added is preferably 0.01% by mass to 5% by mass, more preferably 0.01% by mass to 2.0% by mass, based on the total mass of the toner particles, from the viewpoints of transferability and suppression of image unevenness. Furthermore, in the mixing step, from the viewpoints of transferability and suppression of image unevenness, it is preferable that the amount of large-diameter additive particles added is greater than the amount of small-diameter additive particles added.

[0043] In the toner mixed in the mixing step, from the viewpoints of transferability and suppression of image unevenness, the free ratio, which represents the proportion of the additive particles that are not attached to the toner particles, is preferably 60% or less, more preferably 55% or less, and particularly preferably 10% or more and 50% or less. In addition, in the toner mixed in the mixing step, from the viewpoints of transferability and suppression of image unevenness, the strong adhesion rate, which represents the proportion of additives adhering to the toner after ultrasonic desorption treatment, is preferably 30% or less, more preferably 20% or less, and even more preferably 1% or more and 10% or less, for the large-diameter external additive. Furthermore, in the toner mixed in the mixing step, from the viewpoints of transferability and suppression of image unevenness, the strong adhesion rate, which represents the proportion of additives adhering to the toner after ultrasonic desorption treatment, is preferably 80% or less, more preferably 20% or more and 70% or less, and particularly preferably 25% or more and 60% or less, for the small diameter external additives.

[0044] In addition, in the toner mixed in the mixing step, from the viewpoints of transferability and suppression of image unevenness, it is preferable that the free ratio, which represents the ratio of the additive particles not adhering to the toner particles, is 60% or less, and the strong adhesion ratio, which represents the ratio of the additive particles adhering to the toner after ultrasonic desorption treatment, is 30% or less for the large-diameter external additives and 80% or less for the small-diameter external additives.

[0045] The method for producing the toner for developing electrostatic images according to the present embodiment may further include known steps other than the mixing step. Specifically, for example, the steps shown below can be mentioned. The method for producing the toner for developing electrostatic images according to the embodiment preferably includes a preparation step of preparing toner particles containing an amorphous resin.

[0046] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation-coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). The method for producing the toner particles is not particularly limited, and a well-known production method is adopted. Among these, from the viewpoint of easily producing toner particles having high image quality and high reliability, it is preferable to obtain toner particles by the aggregation and coalescence method.

[0047] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, A step of preparing an amorphous resin particle dispersion liquid in which amorphous resin particles are dispersed, and a crystalline resin particle dispersion liquid in which crystalline resin particles are dispersed (a resin particle dispersion preparation step); a step of aggregating amorphous resin particles (crystalline resin particles, colorant particles, release agent particles, etc., as necessary) in an amorphous resin particle dispersion (in a dispersion obtained by mixing a crystalline resin particle dispersion, a colorant particle dispersion, and a release agent particle dispersion, as necessary) to form first aggregated particles (first aggregated particle forming step); a step of mixing the aggregated particle dispersion liquid with an amorphous resin particle dispersion liquid after obtaining the aggregated particle dispersion liquid in which the first aggregated particles are dispersed, and aggregating the first aggregated particles so that the amorphous resin particles are attached to the surfaces of the first aggregated particles to form second aggregated particles (second aggregated particle step); a step of heating the aggregated particle dispersion liquid in which the second aggregated particles are dispersed to fuse and coalesce the aggregated particles to form toner particles (a fusion and coalescence step); The toner particles are produced through the above steps.

[0048] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.

[0049] -Resin particle dispersion preparation process- First, in addition to each resin particle dispersion liquid (amorphous resin particle dispersion liquid and crystalline resin particle dispersion liquid) in which each resin particle that will become the binder resin is dispersed, for example, a colorant particle dispersion liquid in which colorant particles are dispersed and a release agent particle dispersion liquid in which release agent particles are dispersed are prepared.

[0050] Here, the resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0051] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0052] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0053] In the resin particle dispersion, examples of the method for dispersing the resin particles in the dispersion medium include general dispersion methods using, for example, a rotary shear type homogenizer, a ball mill having a media, a sand mill, a dyno mill, etc. Depending on the type of resin particles, the resin particles may be dispersed in the resin particle dispersion using, for example, a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to effect conversion of the resin from W / O to O / W (so-called phase inversion), resulting in a discontinuous phase, and the resin is dispersed in particulate form in the aqueous medium.

[0054] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are also measured in the same manner.

[0055] The content of the resin particles in the resin particle dispersion is, for example, preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0056] In addition, for example, a colorant particle dispersion and a release agent particle dispersion are also prepared in the same manner as the resin particle dispersion. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0057] -First agglomerated particle formation process- Next, the colorant particle dispersion and the release agent particle dispersion are mixed together with the amorphous resin particle dispersion. Then, in the mixed dispersion, the amorphous resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form first aggregate particles containing the amorphous resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0058] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature of the glass transition temperature of the resin particles (specifically, for example, a temperature of the glass transition temperature of the resin particles -30°C or more and the glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form first aggregated particles. In the first aggregate particle formation step, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, the above-mentioned aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the above-mentioned heating may be carried out.

[0059] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant used as the dispersant added to the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. In particular, when a metal complex is used as the flocculant, the amount of surfactant used is reduced and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ions of the flocculant may be used, and a chelating agent is preferably used as this additive.

[0060] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, such as oxycarboxylic acid (e.g., tartaric acid, citric acid, gluconic acid, etc.), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the amorphous resin particles.

[0061] -Second agglomerated particle formation process- After obtaining the aggregated particle dispersion in which the first aggregated particles are dispersed, the aggregated particle dispersion and the amorphous resin particle dispersion are mixed together.

[0062] Then, in the dispersion liquid in which the first aggregated particles and the amorphous resin particles are dispersed, the amorphous resin particles are aggregated on the surfaces of the first aggregated particles. Specifically, for example, in the first aggregate particle formation step, when the first aggregate particles reach a target particle size, a dispersion of amorphous resin particles is added to the dispersion of the first aggregate particles, and the dispersion is heated at a temperature equal to or lower than the glass transition temperature of the amorphous resin particles. The pH of the dispersion is then adjusted to stop the progression of aggregation.

[0063] -Fusion / unification process- Next, the second aggregate particle dispersion liquid in which the second aggregate particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the amorphous resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the amorphous resin particles) to fuse and coalesce the aggregate particles, thereby forming toner particles.

[0064] Through the above steps, toner particles are obtained.

[0065] After the fusion and coalescence process, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain toner particles in a dried state. In the washing step, it is preferable to carry out sufficient replacement washing with ion-exchanged water from the viewpoint of electrostatic charge. In addition, the solid-liquid separation step is not particularly limited, but it is preferable to carry out suction filtration, pressure filtration, etc. from the viewpoint of productivity. In addition, in the drying step, there is no particular limit to the method, but it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc. from the viewpoint of productivity.

[0066] Hereinafter, each component contained in the toner for developing electrostatic images other than those described above will be described in detail.

[0067] <Binding resin> The binder resin preferably contains an amorphous resin, and more preferably contains an amorphous resin and a crystalline resin from the viewpoints of image strength and suppression of uneven density in the obtained image. That is, in the aggregation step, it is more preferable that the binder resin particles contain an amorphous resin particle and a crystalline resin particle. The toner particles contain an amorphous resin. Furthermore, the toner particles are preferably core-shell type toner particles.

[0068] Here, the term "amorphous resin" refers to a resin that, in a thermal analysis measurement using differential scanning calorimetry (DSC), has only a stepwise endothermic change rather than a clear endothermic peak, is a solid at room temperature, and is thermoplasticized at a temperature equal to or higher than the glass transition temperature. On the other hand, a crystalline resin refers to a resin that has a clear endothermic peak rather than a stepwise change in endothermic amount in differential scanning calorimetry (DSC). Specifically, for example, a crystalline resin means a resin whose half-width of an endothermic peak is within 10°C when measured at a heating rate of 10°C / min, and an amorphous resin means a resin whose half-width exceeds 10°C or a resin in which no clear endothermic peak is observed.

[0069] The amorphous resin will be described. Examples of the amorphous resin include known amorphous resins such as amorphous polyester resin, amorphous vinyl resin (e.g., styrene acrylic resin, etc.), epoxy resin, polycarbonate resin, polyurethane resin, etc. Among these, from the viewpoint of suppressing uneven density and suppressing white spots in the obtained image, amorphous polyester resin and amorphous vinyl resin (particularly styrene acrylic resin) are preferred, and amorphous polyester resin is more preferred. In addition, it is also a preferred embodiment to use an amorphous polyester resin and a styrene-acrylic resin in combination as the amorphous resin.

[0070] The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0071] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acid. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0072] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, aromatic diols and alicyclic diols are preferred as polyhydric alcohols, and aromatic diols are more preferred. As the polyhydric alcohol, a trihydric or higher polyhydric alcohol having a crosslinked or branched structure may be used in combination with the diol. Examples of the trihydric or higher polyhydric alcohol include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0073] The amorphous polyester resin is obtained by a known manufacturing method. Specifically, for example, the polymerization temperature is set to 180°C or more and 230°C or less, the reaction system is depressurized as necessary, and the reaction is carried out while removing water and alcohol generated during condensation. If the raw material monomer is not dissolved or compatible at the reaction temperature, a high-boiling point solvent may be added as a dissolution aid to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the dissolution aid. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed with the monomer and then polycondensed with the main component.

[0074] As the binder resin, particularly the amorphous resin, a styrene-acrylic resin can be mentioned. The styrene-acrylic resin is a copolymer obtained by copolymerizing at least a styrene-based monomer (a monomer having a styrene skeleton) and a (meth)acrylic-based monomer (a monomer having a (meth)acrylic group, preferably a monomer having a (meth)acryloxy group). The styrene-acrylic resin includes, for example, a copolymer of a styrene monomer and a (meth)acrylic acid ester monomer. The acrylic resin portion of the styrene-acrylic resin is a partial structure formed by polymerizing either an acrylic monomer or a methacrylic monomer, or both. In addition, the term "(meth)acrylic" includes both "acrylic" and "methacrylic".

[0075] Specific examples of styrene-based monomers include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.

[0076] Specific examples of the (meth)acrylic monomer include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, and (meth) Examples of the (meth)acrylic acid monomer include neopentyl acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate esters (e.g., phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomer may be used alone or in combination of two or more. Among these (meth)acrylic esters among the (meth)acrylic monomers, from the viewpoint of fixation, (meth)acrylic acid esters having an alkyl group having 2 to 14 carbon atoms (preferably 2 to 10 carbon atoms, more preferably 3 to 8 carbon atoms) are preferred. Of these, n-butyl (meth)acrylate is preferred, and n-butyl acrylate is particularly preferred.

[0077] The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) is not particularly limited, but is preferably 85 / 15 to 70 / 30.

[0078] The styrene-acrylic resin may have a crosslinked structure. A preferred example of the styrene-acrylic resin having a crosslinked structure is a copolymer of at least a styrene-based monomer, a (meth)acrylic acid-based monomer, and a crosslinkable monomer.

[0079] The crosslinkable monomer may, for example, be a bifunctional or higher functional crosslinking agent. Examples of bifunctional crosslinking agents include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylene bis(meth)acrylamide, decanediol diacrylate, glycidyl (meth)acrylate, etc.), polyester type di(meth)acrylate, 2-([1'-methylpropylideneamino]carboxyamino)ethyl methacrylate, etc. Examples of polyfunctional crosslinking agents include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., pentaerythritol tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendate, etc. Among these, as the crosslinkable monomer, from the viewpoints of suppressing the occurrence of a decrease in image density and suppressing the occurrence of uneven image density, and of fixability, a bifunctional or higher (meth)acrylate compound is preferred, a bifunctional (meth)acrylate compound is more preferred, a bifunctional (meth)acrylate compound having an alkylene group having 6 to 20 carbon atoms is even more preferred, and a bifunctional (meth)acrylate compound having a linear alkylene group having 6 to 20 carbon atoms is particularly preferred.

[0080] The copolymerization ratio of the crosslinkable monomer to the total monomers (mass basis, crosslinkable monomer / total monomers) is not particularly limited, but is preferably 2 / 1,000 to 20 / 1,000.

[0081] The method for producing the styrene-acrylic resin is not particularly limited, and various polymerization methods (e.g., solution polymerization, precipitation polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc.) are applied. In addition, the polymerization reaction is carried out by a known operation (e.g., batchwise, semi-continuous, continuous, etc.).

[0082] The proportion of the styrene-acrylic resin in the total binder resin is preferably from 0% to 20% by mass, more preferably from 1% to 15% by mass, and even more preferably from 2% to 10% by mass.

[0083] The proportion of the amorphous resin in the total binder resin is preferably 60% by mass or more and 98% by mass or less, more preferably 65% ​​by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 90% by mass or less.

[0084] The characteristics of the amorphous resin will be described. The glass transition temperature (Tg) of the amorphous resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."

[0085] The weight average molecular weight (Mw) of the amorphous resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0086] The crystalline resin will now be described. Examples of the crystalline resin include known crystalline resins such as crystalline polyester resins and crystalline vinyl resins (e.g., polyalkylene resins, long-chain alkyl (meth)acrylate resins, etc.). Among these, crystalline polyester resins are preferred from the viewpoint of suppressing uneven density and white spots in the resulting image.

[0087] The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Since the crystalline polyester resin easily forms a crystalline structure, a polycondensation product using a straight-chain aliphatic polymerizable monomer is preferable to a polymerizable monomer having an aromatic ring.

[0088] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower (e.g., carbon number 1 to 5) alkyl esters. As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0089] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0090] The polyhydric alcohol may have an aliphatic diol content of 80 mol % or more, and preferably 90 mol % or more.

[0091] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature of the crystalline polyester resin is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0092] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0093] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester resin.

[0094] As the crystalline polyester resin, a polymer of an α,ω-linear aliphatic dicarboxylic acid and an α,ω-linear aliphatic diol is preferred from the viewpoint of easily forming a crystal structure and having good compatibility with the amorphous polyester resin, thereby improving the fixability of the image.

[0095] The α,ω-linear aliphatic dicarboxylic acid is preferably an α,ω-linear aliphatic dicarboxylic acid in which the alkylene group connecting the two carboxy groups has 3 or more and 14 or less carbon atoms, more preferably the alkylene group has 4 or more and 12 or less carbon atoms, and even more preferably the alkylene group has 6 or more and 10 or less carbon atoms. Examples of α,ω-linear aliphatic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, 1,6-hexanedicarboxylic acid (commonly known as suberic acid), 1,7-heptanedicarboxylic acid (commonly known as azelaic acid), 1,8-octanedicarboxylic acid (commonly known as sebacic acid), 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid. Of these, 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, and 1,10-decanedicarboxylic acid are preferred. The α,ω-linear aliphatic dicarboxylic acids may be used alone or in combination of two or more kinds.

[0096] The α,ω-linear aliphatic diol is preferably an α,ω-linear aliphatic diol in which the alkylene group connecting the two hydroxy groups has 3 to 14 carbon atoms, more preferably the alkylene group has 4 to 12 carbon atoms, and further preferably the alkylene group has 6 to 10 carbon atoms. Examples of the α,ω-linear aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol. Of these, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred. The α,ω-linear aliphatic diols may be used alone or in combination of two or more kinds.

[0097] As the polymer of an α,ω-linear aliphatic dicarboxylic acid and an α,ω-linear aliphatic diol, from the viewpoint of easily forming a crystal structure and having good compatibility with an amorphous polyester resin, thereby improving the fixability of an image, a polymer of at least one selected from the group consisting of 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid, and 1,10-decanedicarboxylic acid and at least one selected from the group consisting of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol is preferred, and among these, a polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol is more preferred.

[0098] The proportion of the crystalline resin in the total binder resin is preferably from 1% by mass to 20% by mass, more preferably from 2% by mass to 15% by mass, and even more preferably from 3% by mass to 10% by mass.

[0099] Other binder resins Examples of the binder resin include homopolymers of monomers such as ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.) and olefins (e.g., ethylene, propylene, butadiene, etc.), and copolymers of two or more of these monomers. Other examples of the binder resin include non-vinyl resins such as epoxy resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0100] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0101] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0102] As the release agent, from the viewpoints of suppressing uneven density and white voids in the obtained image and having good compatibility with the amorphous polyester resin, thereby improving the fixability of the image, an ester wax is preferred, and an ester wax of a higher fatty acid having from 10 to 30 carbon atoms and a monovalent or polyvalent alcohol component having from 1 to 30 carbon atoms is more preferred.

[0103] The ester wax is a wax having an ester bond. The ester wax may be any of a monoester, diester, triester, and tetraester, and any known natural or synthetic ester wax can be used. Examples of ester waxes include ester compounds of higher fatty acids (such as fatty acids having 10 or more carbon atoms) and monohydric or polyhydric aliphatic alcohols (such as aliphatic alcohols having 8 or more carbon atoms), and have a melting temperature of 60°C or higher and 110°C or lower (preferably 65°C or higher and 100°C or lower, more preferably 70°C or higher and 95°C or lower). Examples of ester waxes include ester compounds of higher fatty acids (caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, etc.) and alcohols (monohydric alcohols such as methanol, ethanol, propanol, isopropanol, butanol, capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, oleyl alcohol, etc.; polyhydric alcohols such as glycerin, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, etc.). Specific examples include carnauba wax, rice wax, candelilla wax, jojoba oil, Japan wax, beeswax, privet wax, lanolin, and montanic acid ester wax.

[0104] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0105] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0106] -Coloring agent- In the aggregating step, it is preferable that the dispersion liquid further contains colorant particles. Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0107] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0108] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0109] -Other additives- Examples of other additives include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0110] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a so-called core-shell structure (core-shell type particles) composed of a core (core particle) and a coating layer (shell layer) that coats the core. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, a colorant and a release agent, and a coating layer containing a binder resin. In the case of toner particles having a core-shell structure, the average thickness of the shell layer is preferably 120 nm or more, more preferably 130 nm or more, and even more preferably 140 nm or more, from the viewpoint of suppressing deformation of the toner particles, and is preferably 550 nm or less, more preferably 500 nm or less, and even more preferably 400 nm or less.

[0111] The average thickness of the shell layer is measured by the following method. Toner particles are embedded in epoxy resin, sliced ​​using a diamond knife or the like, and the slices are stained with osmium tetroxide or ruthenium tetroxide in a desiccator. The stained slices are observed under a scanning electron microscope (SEM). Ten toner particle cross sections are randomly selected from the SEM images, and the shell layer thickness is measured at 20 points per toner particle, the average value is calculated, and the average value of the 10 toner particles is regarded as the average thickness.

[0112] Toner volume average particle size (D 50v ) is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.

[0113] The volume average particle size of the toner is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 mL of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 mL to 150 mL of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size of each particle in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture of 100 μm in diameter. The number of particles sampled is 50,000. For the measured particle size, a cumulative distribution based on volume is drawn from the smallest diameter side, and the particle size at which the cumulative 50% occurs is called the volume average particle size D 50v It is defined as:

[0114] In this embodiment, the average circularity of the toner particles is not particularly limited, but from the viewpoint of improving the cleaning properties of the toner from the image carrier, it is preferably 0.91 or more and 0.98 or less, more preferably 0.94 or more and 0.98 or less, and even more preferably 0.95 or more and 0.97 or less.

[0115] In this embodiment, the circularity of a toner particle is the perimeter of a circle having the same area as the projected image of the particle divided by the perimeter of the projected image of the particle, and the average circularity of a toner particle is the cumulative circularity of 50% from the smallest side in the distribution of circularity. The average circularity of a toner particle is determined by analyzing at least 3,000 toner particles using a flow-type particle image analyzer.

[0116] The average circularity of the toner particles can be controlled, for example, by adjusting the stirring speed of the dispersion, the temperature of the dispersion, or the retention time in the fusing step.

[0117] The amount of release agent on the toner particle surface can be controlled by, for example, adjusting the amount of release agent charged, the type of release agent, the temperature during melting and kneading, or by performing surface treatment with hot air after pulverization.

[0118] <Electrostatic image developer> The electrostatic image developer according to this embodiment contains at least the toner produced by the method for producing a toner for developing electrostatic images according to this embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner produced by the method for producing a toner for developing electrostatic images according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.

[0119] The carrier is not particularly limited, and may be any known carrier, such as a coated carrier in which the surface of a core material made of magnetic powder is coated with a coating resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, or a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material and are coated with a coating resin.

[0120] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.

[0121] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing an organosiloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, and epoxy resin. The coating resin and the matrix resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0122] Here, in order to coat the surface of the core material with a coating resin, a method of coating with a coating layer forming solution in which the coating resin and, if necessary, various additives are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the coating resin to be used, the suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer, a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material, a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air, and a kneader coater method in which the core material of a carrier and the solution for forming a coating layer are mixed in a kneader coater and the solvent is removed.

[0123] In the two-component developer, the mixture ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0124] <Image forming device / image forming method> An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0125] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0126] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is then secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder before charging after the transfer of the toner image; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it before charging after the transfer of the toner image. Among them, an image forming apparatus equipped with a cleaning means for cleaning the surface of the image carrier is preferable, and a cleaning blade is preferable as the cleaning means. In the case of an intermediate transfer type device, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0127] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a developing means that contains the electrostatic image developer according to the present embodiment is preferably used.

[0128] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.

[0129] FIG. 10 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 10 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.

[0130] Above each of the units 10Y, 10M, 10C, and 10K in the drawing, an intermediate transfer belt 20 is provided as an intermediate transfer body extending through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are arranged from left to right in the drawing at a distance from each other and contact the inner surface of the intermediate transfer belt 20, and is adapted to run in a direction from the first unit 10Y to the fourth unit 10K. Note that a force is applied to the support roll 24 in a direction away from the drive roll 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around them. In addition, an intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. Further, the developing devices (developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with toner including four colors of toner, yellow, magenta, cyan, and black, contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0131] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative example. Note that by assigning reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y) to parts equivalent to those of the first unit 10Y, descriptions of the second to fourth units 10M, 10C, and 10K will be omitted.

[0132] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. Furthermore, a bias power supply (not shown) that applies a primary transfer bias is connected to each of the primary transfer rolls 5Y, 5M, 5C, and 5K. Each bias power supply varies the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0133] Hereinafter, an operation of forming a yellow image in first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity at 20° C. of 1×10 -6The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam 3Y, the resistivity of the portion irradiated with the laser beam changes. A laser beam 3Y is output to the charged surface of the photoreceptor 1Y via an exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). The laser beam 3Y is irradiated onto the photosensitive layer on the surface of the photoreceptor 1Y, and an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0134] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y is rotated to a predetermined developing position as the photoconductor 1Y travels. Then, at this developing position, the electrostatic image on the photoconductor 1Y is made visible as a toner image (developed image) by the developing device 4Y.

[0135] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0136] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and in the first unit 10Y, for example, it is controlled to +10 μA by a control unit (not shown). On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0137] Further, the primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of the respective colors are transferred in a superimposed manner.

[0138] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0139] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0140] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets, etc. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.

[0141] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0142] <Process cartridge / toner cartridge> The process cartridge according to this embodiment will be described. The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.

[0143] In addition, the process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.

[0144] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.

[0145] FIG. 11 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 11 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 11, 109 indicates an exposure device (an example of an electrostatic image forming means), 112 indicates a transfer device (an example of a transfer means), 115 indicates a fixing device (an example of a fixing means), and 300 indicates recording paper (an example of a recording medium).

[0146] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.

[0147] 10 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K can be attached and detached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) through toner supply pipes (not shown). When the toner contained in the toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES

[0148] Hereinafter, the present embodiment will be described in more detail with reference to examples and comparative examples, but the present embodiment is not limited to these examples. Note that "parts" and "%" indicating amounts are based on mass unless otherwise specified.

[0149] [Synthesis of polyester resin 1] In a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen gas inlet tube, 80 mol parts of polyoxypropylene (2,2)-2,2-bis (4-hydroxyphenyl) propane, 10 mol parts of ethylene glycol, 10 mol parts of cyclohexanediol, 80 mol parts of terephthalic acid, 10 mol parts of isophthalic acid and 10 mol parts of n-dodecenyl succinic acid were charged, and the reaction vessel was replaced with dry nitrogen gas. Then, 0.25 mass parts of titanium tetrabutoxide was charged as a catalyst with respect to 100 mass parts of the monomer component. After stirring and reacting for 3 hours at 170°C under a nitrogen gas flow, the temperature was further raised to 210°C over 1 hour, the pressure in the reaction vessel was reduced to 3 kPa, and the reaction was stirred and reacted under reduced pressure for 13 hours to obtain a polyester resin. The glass transition temperature of the obtained resin was measured using a differential scanning calorimeter (DSC) and found to be 56°C.

[0150] [Synthesis of polyester resin 2] Except for changing the amount of titanium tetrabutoxide used as a catalyst to 0.50 parts by mass relative to 100 parts by mass of the monomer components, polyester resin 2 was prepared in the same manner as polyester resin 1. The glass transition temperature of the obtained resin was measured using a differential scanning calorimeter (DSC) and found to be 48°C.

[0151] [Preparation of Polyester Resin Particle Dispersion 1] Next, 200 parts by mass of polyester resin 1, 100 parts by mass of methyl ethyl ketone, and 70 parts by mass of isopropyl alcohol were placed in a jacketed reaction vessel equipped with a condenser, a thermometer, a water dropping device, and an anchor blade, and the resin was dissolved while stirring and mixing at 100 rpm while maintaining at 70 ° C. in a water circulation type thermostatic bath. Thereafter, the stirring speed was set to 150 rpm, the water circulation type thermostatic bath was set to 66 ° C., and 10 parts of 10% ammonia water (reagent) were added over 10 minutes, and then a total of 600 parts by mass of ion-exchanged water kept at 66 ° C. was dropped at a rate of 5 parts by mass / min to cause phase inversion, thereby obtaining an emulsion. 600 parts of the obtained emulsion and 525 parts by mass of ion-exchanged water were placed in an eggplant flask, and set in an evaporator equipped with a vacuum control unit via a trap bulb. While rotating the eggplant flask, it was heated in a hot water bath at 60 ° C., and the pressure was reduced to 7 kPa while paying attention to bumping, and the solvent was removed. When the amount of recovered solvent reached 825 parts, the pressure was returned to normal and the recovery flask was cooled with water to obtain a dispersion liquid. Ion-exchanged water was added to obtain polyester resin particle dispersion liquid 1 having a solid content concentration of 20 mass %.

[0152] [Preparation of Polyester Resin Particle Dispersion 2] Polyester resin particle dispersion 2 was prepared in the same manner as polyester resin particle dispersion 1, except that polyester resin 1 was changed to polyester resin 2.

[0153] [Preparation of Release Agent Particle Dispersion 1] Paraffin wax (manufactured by Nippon Seiro Co., Ltd., FNP92, endothermic peak onset 81°C): 45 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts - Ion-exchanged water: 200 parts The above was mixed and heated to 95°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). After that, it was dispersed using a Manton-Gaulin high pressure homogenizer (Gaulin) to prepare release agent particle dispersion 1 (solid content: 20%) in which the release agent was dispersed. The volume average particle size of the release agent particles was 0.19 μm.

[0154] [Preparation of Release Agent Particle Dispersion 2] Paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-9, endothermic peak onset: 67°C): 45 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts - Ion-exchanged water: 200 parts The above was mixed and heated to 90°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). After that, it was dispersed using a Manton-Gaulin high pressure homogenizer (Gaulin) to prepare a release agent particle dispersion 2 (solid content concentration: 20%) in which the release agent was dispersed. The volume average particle size of the release agent particles was 0.23 μm.

[0155] [Preparation of Colorant Particle Dispersion] Cyan pigment (Dainichi Seikagaku Co., Ltd., Pigment Blue 15:3 (copper phthalocyanine)): 98 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen R): 2 parts Ion-exchanged water: 400 parts The above ingredients were mixed and dissolved, and dispersed for 10 minutes using a homogenizer (IKA Ultra Turrax), to obtain a colorant particle dispersion having a median particle size of 0.16 μm and a solid content of 20%.

[0156] [Preparation of Carrier] 100 parts of ferrite particles (manufactured by Powder Tech Co., Ltd., average particle size 50 μm) and 1.5 parts of polymethyl methacrylate resin (manufactured by Mitsubishi Rayon Co., Ltd., weight average molecular weight 95,000, the ratio of components with weight average molecular weight of 10,000 or less is 5%) were placed in a pressure kneader together with 500 parts of toluene, stirred and mixed at room temperature for 15 minutes, and then heated to 70°C while mixing under reduced pressure to distill off the toluene, and then cooled and classified using a 105 μm sieve to obtain a resin-coated ferrite carrier.

[0157] Example 1 [Toner Preparation] - Preparation of toner particles (1) - Polyester resin particle dispersion 1:100 parts by weight Colorant particle dispersion: 10 parts by weight Release agent particle dispersion 1:9 parts by weight Anionic surfactant (Tayca Power BN2060, manufactured by Tayca Corporation): 1 part by weight Ion-exchanged water: 200 parts by weight The above raw materials were placed in a cylindrical stainless steel container, and 3 parts of a 0.3 M (=0.3 mol / L) aqueous nitric acid solution was added to adjust the pH to 3.0. Next, 50 parts of a 10% aqueous solution of aluminum sulfate was added dropwise as a flocculant while applying a shear force at 6,000 rpm using an Ultraturrax (manufactured by IKA), and the mixture was stirred for 5 minutes. Next, the raw material mixture was heated to 45°C with a mantle heater and held for 30 minutes, after which a resin particle dispersion for coating, prepared by mixing 25 parts of polyester resin particle dispersion 1 and 10 parts of ion-exchanged water and adjusting the pH to 3.0, was added and held for 10 minutes. Then, in order to stop the growth of the coated aggregated particles (adhered particles), a 1M (=1mol / L) aqueous sodium hydroxide solution was added to control the pH of the raw material mixture to 8.0. Next, in order to fuse the aggregated particles, the temperature was raised to 90°C at a heating rate of 1°C / min. After reaching 90°C, the mixture was held for 4 hours. Then, the mixture was cooled to 40°C to obtain toner slurry A1. Next, the toner particles dispersed in the aqueous solution were filtered, washed with ion-exchanged water, and then subjected to solid-liquid separation by Nutsche suction filtration. This was further redispersed in 3 L of ion-exchanged water at 40°C, stirred at 300 rpm for 15 minutes, and washed. This was repeated five more times, after which solid-liquid separation was carried out using No. 5A filter paper by Nutsche suction filtration, and the obtained solid matter was vacuum dried for 12 hours to obtain toner particles 1 having a volume average particle size of 6.1 μm.

[0158] [Preparation of Silica Particles (1)] SiCl4, hydrogen gas, and oxygen gas are mixed in the mixing chamber of a combustion burner and then burned at a temperature between 1,000°C and 3,000°C. Silica particles are obtained by extracting silica powder from the gas after combustion. At this time, the molar ratio of hydrogen gas and oxygen gas is 1.3:1 to obtain silica particles (R1) with a volume average particle size of 136 nm. 100 parts of the obtained silica particles (R1) and 500 parts of ethanol were placed in an evaporator and stirred for 15 minutes while maintaining the temperature at 40° C. Next, 20 parts of hexamethyldisilazane (HMDS) were added to 100 parts of silica particles and stirred for 15 minutes. Finally, the temperature was raised to 90° C. and the ethanol was dried under reduced pressure. After that, the treated product was taken out and further vacuum dried at 120° C. for 30 minutes to obtain silica particles (1) treated with hexamethyldisilazane and having a volume average particle size of 136 nm.

[0159] Next, a Henschel mixer FM75J / I manufactured by Mitsui Mining Co., Ltd. was used as the additive mixing device, and the mixing blades used were the blade shown as Z0 (upper) in FIG. 6 (upper blade: second mixing blade) and the blade shown as B0 (lower) in FIG. 5 (lower blade: first mixing blade). Toner particles 1:100 mass parts were added with 5 parts of silica particles (1) and 1.0 part of titanium oxide particles (average primary particle size 15 nm, JMT-150IB, manufactured by Teika Co., Ltd.) as external additives, and mixed for 35 minutes in the Henschel mixer so that the temperature setting value in the mixer at which cooling was started, the value of (Pm-P0) / w, and the value of (Pm-P0)·t / w were the values ​​shown in Table 1. The temperature Ti in the mixer was an initial temperature of 25°C, a maximum temperature of 55°C, and a final temperature (Te) of 46°C. After that, the second and subsequent mixings were performed continuously under the same conditions, and the absolute values ​​of the difference between the second and subsequent mixings and the first mixing (|Ten-Te1| and |Tan-Ta1|) were both 1°C or less. Next, the mixture was sifted using a wind sifter (Hivolter 300, manufactured by Shin Tokyo Kikai Co., Ltd.) to obtain toner 1 (toner for developing electrostatic images).

[0160] Next, the liberation rate of additive particles in Toner 1 was measured by the following method. 4 g of the toner to be measured was added to 50 mL of a 0.5% aqueous solution of surfactant (Noigen ET-165, Daiichi Kogyo Seiyaku Co., Ltd.) to be measured, and the mixture was stirred for 5 minutes at 100 rpm with a magnetic stirrer to prepare a toner dispersion. Next, the toner dispersion was centrifuged for 2 minutes at 3,000 rpm with a centrifuge to remove the supernatant. After that, 50 mL of ion-exchanged water was added to the precipitated toner to disperse it again, and the dispersion was suction filtered (Kiriyama funnel filter paper No. 5C 60φm / m, Kiriyama Seisaku Co., Ltd.), the toner remaining on the filter paper was collected, 50 mL of ion-exchanged water was added, the toner was dispersed, and the mixture was suction filtered and washed. After washing, the toner remaining on the filter paper was collected and dried in a 40°C thermostatic chamber for 12 hours. 3 g of the obtained toner was molded into pellets with a diameter of 30 mm and a thickness of 2 mm under conditions of a load of 10 t and a pressure time of 60 seconds using an automatic pressure molding machine (BRE-32, manufactured by Mayekawa Test Machinery Manufacturing Co., Ltd.) to obtain sample 1. Next, a toner that was not subjected to the above treatment was molded into pellets with a diameter of 30 mm and a thickness of 2 mm under conditions of a load of 10 t and a pressure time of 60 seconds to obtain sample 2. Furthermore, the toner particles before mixing with the additive particles were also molded under pressure to obtain sample 0. Next, quantitative analysis of the constituent elements of the additive was performed using a fluorescent X-ray device (ZSX-100e, manufactured by Rigaku Corporation). The metal element content of each sample was measured. The metal element content was calculated by a calibration curve prepared in advance. Using these values, the liberation rate was calculated by the following formula (A). Formula (A) Release rate={(C2-C1) / (C1-C0)×100} In formula (A), C0 represents the metal element content of sample 0, C1 represents the metal element content of sample 1, and C2 represents the metal element content of sample 2.

[0161] The strong adhesion rate of the additive particles in the toner 1 was measured by the following method. 4 g of the toner to be measured was added to 50 mL of a 0.5% surfactant (Noigen ET-165, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) aqueous solution to be measured, and the mixture was stirred for 5 minutes at 100 rpm with a magnetic stirrer to prepare a toner dispersion. Next, ultrasonic desorption treatment was performed on this toner dispersion. Ultrasonic vibration was applied to the toner dispersion using an ultrasonic homogenizer (VCX750, manufactured by Sonic and Material Co., Ltd.) (ultrasonic vibration part height from the bottom surface 1.0 cm, intensity 40 W, 10 minutes). Next, this toner dispersion was centrifuged with a centrifuge at 3,000 rpm for 2 minutes, and the supernatant was removed. After that, 50 mL of ion-exchanged water was added to the precipitated toner to disperse it again, and the dispersion was suction filtered (Kiriyama funnel filter paper No. 5C 60φm / m, manufactured by Kiriyama Seisakusho Co., Ltd.), and the toner remaining on the filter paper was collected, 50 mL of ion-exchanged water was added to disperse it, and suction filtration was performed to wash it. After washing, the toner remaining on the filter paper was collected and dried in a 40°C thermostatic chamber for 12 hours. 3 g of the obtained toner was molded into pellets with a diameter of 30 mm and a thickness of 2 mm under conditions of a load of 10 t and a pressure time of 60 seconds using an automatic pressure molding machine (BRE-32, manufactured by Mayekawa Test Machinery Manufacturing Co., Ltd.) to obtain Sample 1. Next, a toner that had not been subjected to the above treatment was molded into pellets with a diameter of 30 mm and a thickness of 2 mm under conditions of a load of 10 t and a pressure time of 60 seconds to obtain Sample 2. Furthermore, the toner particles before mixing with the additive particles were also molded under pressure to obtain Sample 0. Next, a quantitative analysis of the constituent elements of the additive was performed using a fluorescent X-ray device (ZSX-100e, manufactured by Rigaku Corporation). The metal element content of each sample was measured. The metal element content was calculated by a calibration curve prepared in advance. Using these values, the strong adhesion rate was calculated by the following formula (B). Formula (B) Strong adhesion rate = {(C1-C0) / (C2-C0) x 100} (Here, C0 represents the metal element content of sample 0, C1 represents the metal element content of sample 1, and C2 represents the metal element content of sample 2.)

[0162] [Mixing Toner and Carrier] The obtained toner 1 and carrier were placed in a V blender in a ratio of toner:carrier=5:95 (mass ratio) and stirred for 20 minutes to obtain developer 1 (electrostatic image developer).

[0163] (Examples 2 to 12 and Comparative Examples 1 to 3) A toner and a developer were prepared in the same manner as in Example 1, except that the various conditions in the mixing step were changed as shown in Table 1 or Table 2.

[0164] Example 13 [Preparation of Silica Particles (2)] Silica particles (2) having a volume average particle size of 82 nm were obtained under the same conditions and by the same method as for silica particles (1), except that the molar ratio of hydrogen gas to oxygen gas was 1.6:1.

[0165] A toner and a developer were prepared in the same manner as in Example 1, except that the silica particles (1) were replaced with silica particles (2) as the external additive in the mixing step. The various conditions are shown in Table 2.

[0166] Example 14 A toner and a developer were prepared in the same manner as in Example 1, except that the titanium oxide particles (average primary particle size 15 nm, JMT-150IB, manufactured by Teika Co., Ltd.) were replaced with titanium oxide particles (average primary particle size 40 nm, STT-30EHJ, manufactured by Titan Kogyo Co., Ltd.) as the external additive in the mixing process.

[0167] Example 15 - Preparation of toner particles (2) - Toner particles (2) were produced in the same manner as toner particles (1), except that polyester resin particle dispersion 1 was changed to polyester resin particle dispersion 2. The volume average particle size was 6.2 μm.

[0168] A toner and a developer were prepared in the same manner as in Example 1, except that toner particles 1 were changed to toner particles 2 in the mixing step.

[0169] Example 16 The toner and developer were each prepared in the same manner as in Example 1, except that the additive mixing device in the mixing process was changed from the Henschel Mixer FM75J / I manufactured by Mitsui Mining Co., Ltd. to a Loedige Mixer (manufactured by Matsubo Corporation, FKM50D).

[0170] 〔evaluation〕 The resulting developer was used to evaluate the transferability and the ability to suppress image unevenness.

[0171] <Transferability> The developer was loaded into a modified 700 Digital Color Press manufactured by Fuji Xerox Co., Ltd. The toner load on the photoconductor was 5 g / m 2 The development potential was adjusted so that the image area ratio was 5%, and 1,000 sheets of A4-sized plain paper were continuously printed under low temperature and low humidity (temperature 10°C / relative humidity 20%). When printing one sheet next, the evaluation machine was stopped immediately after the toner image on the photoconductor was transferred to the intermediate transfer body (intermediate transfer belt) (i.e., before cleaning the photoconductor). The toner remaining on the photoconductor without being transferred was removed with mending tape and its weight was measured. The initial transfer efficiency was calculated from the amount of toner applied during development and the amount of toner remaining, using the following formula (A), and was classified as follows. A and B are within the acceptable range. Formula (A): Transfer efficiency = (toner amount applied during development - toner remaining amount) ÷ toner amount applied during development x 100 -Evaluation criteria- A: Transfer efficiency is 98% or more B: Transfer efficiency is 95% or more and less than 98% C: Transfer efficiency is 90% or more but less than 95% D: Transfer efficiency is less than 90%

[0172] <Image unevenness suppression> The developer was filled into the developing device of Fuji Xerox Co., Ltd.'s image forming device "DocuCentre500CP". Using this image forming device, 1,000 solid images with 90% image density, including partial non-image areas, were continuously output on A4 paper in an environment of 10°C and 15% RH. After that, a halftone image with 50% image density was output on A4 paper, and the image density of the output halftone image was measured at 12 points for the non-image areas of the solid image including partial non-image areas and the solid image areas, respectively, using an X-rite densitometer (X-rite404, manufactured by X-rite Co., Ltd.) and the average value was calculated. The difference in image density between the areas corresponding to the non-image areas and the areas corresponding to the solid image areas was calculated, and image unevenness was evaluated. The evaluation criteria are as follows. A and B are within the acceptable range. -Evaluation criteria- A: Image density difference is 0.2 or less B: Image density difference is greater than 0.2 and less than or equal to 0.3 C: Image density difference is greater than 0.3 and less than or equal to 0.4 D: Image density difference is greater than 0.4

[0173] The evaluation results are summarized in Tables 1 and 2.

[0174] [Table 1]

[0175] [Table 2]

[0176] From the above results, it is understood that the present embodiment provides a toner for developing electrostatic images which is superior in transferability and suppression of image unevenness as compared with the comparative example. [Explanation of symbols]

[0177] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 30 Intermediate transfer body cleaning device 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 118 Exposure Aperture 117 Cabinet 200 Process Cartridge 300 Recording paper (an example of a recording medium) P Recording paper (an example of a recording medium) 400 Mixing equipment 401 Cooling water inlet 402 Cooling water outlet 403 Ventilation Filter 404 Deflector 405 Motor 406 Upper blade (mixing blade) 407 Lower blade (mixing blade) 408 Exhaust valve 409 Outlet 410 Temperature Sensor 411 Mixing tank 500 Additive dosing device 502 Weighing Hopper 504 Transport mechanism 506a,506b,506c cutting machine 508a, 508b, 508c Cutting means 510a, 510b, 510c Stirring means 512a,512b,512c Metering and discharging means 600 Mixing equipment 602 Mixing tank 604 Inlet 606 Discharge section

Claims

1. The method includes a mixing step of mixing toner particles containing an amorphous resin with additive particles, The mixing device used in the mixing step has a stirring tank, a stirring blade, and a jacket capable of cooling the stirring tank, The following conditions (1) and (2) are satisfied, In the mixing step, the temperature inside the device at the end of mixing is Te, and the average temperature inside the device from 2 minutes after the start of mixing to the end of mixing is Ta. When the mixing step is carried out two or more times in succession, Te1, which is the Te of the first time, Ten, which is the Te of the nth time, and Ta1, which is the Ta of the first time, and Tan, which is the Ta of the nth time, always satisfy |Ten-Te1|≦5° C. and |Tan-Ta1|≦5° C. A method for producing a toner for developing electrostatic images. Condition (1): The temperature Ti inside the mixer in the mixing step satisfies Tg-50° C.≦Ti<Tg (formula 1), where Tg is the glass transition temperature of the amorphous resin contained in the vicinity of the surfaces of the toner particles. Condition (2): 0.08≦(Pm−P0) / w≦0.50 (Equation 2) is satisfied. In formula 2, Pm represents the average power (kW) of the motor that drives the stirring blade of the mixing device in the mixing process, P0 represents the air power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles in the mixing device. In the above formula, |Ten-Te1| and |Tan-Ta1| represent the absolute values ​​of Ten-Te1 and Tan-Ta1, respectively.

2. The method includes a mixing step of mixing toner particles containing an amorphous resin with additive particles, The mixing device used in the mixing step has a stirring tank, a stirring blade, and a jacket capable of cooling the stirring tank, The following conditions (1) and (3) are satisfied, In the mixing step, the temperature inside the device at the end of mixing is Te, and the average temperature inside the device from 2 minutes after the start of mixing to the end of mixing is Ta. When the mixing step is carried out two or more times in succession, Te1, which is the Te of the first time, Ten, which is the Te of the nth time, and Ta1, which is the Ta of the first time, and Tan, which is the Ta of the nth time, always satisfy |Ten-Te1|≦5° C. and |Tan-Ta1|≦5° C. A method for producing a toner for developing electrostatic images. Condition (1): The temperature Ti inside the mixer in the mixing step satisfies Tg-50° C.≦Ti<Tg (formula 1), where Tg is the glass transition temperature of the amorphous resin contained in the vicinity of the surfaces of the toner particles. Condition (3): 40≦(Pm−P0)·t / w≦300 (Equation 3) is satisfied. In formula 3, t represents the mixing time (sec) in the mixing process, Pm represents the average power (kW) of the motor that drives the stirring blade of the mixing device in the mixing process, P0 represents the air power (kW) of the motor, and w represents the total mass (kg) of the toner particles and the additive particles in the mixing device. In the above formula, |Ten-Te1| and |Tan-Ta1| represent the absolute values ​​of Ten-Te1 and Tan-Ta1, respectively.

3. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein a set value of a temperature inside the mixing device at which cooling is started by passing water through the jacket in the mixing step is a glass transition temperature (Tg) of the amorphous resin −30° C. or higher and a glass transition temperature (Tg) of the amorphous resin −5° C. or lower.

4. 4. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the rotation speed of the stirring blade in the mixing step is 20 m / sec or more and 80 m / sec or less.

5. 5. The method for producing a toner for developing electrostatic images according to claim 1, wherein an internal temperature Te of the apparatus at the end of mixing in the mixing step is equal to or higher than a glass transition temperature Tg of the amorphous resin −25° C. and equal to or lower than a glass transition temperature Tg of the amorphous resin −10° C.

6. 6. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the additive particles contain one or more types of large-diameter additive particles having an arithmetic mean particle size of 60 nm or more and two or more types of small-diameter additive particles having an arithmetic mean particle size of less than 60 nm.

7. 7. The method for producing a toner for developing electrostatic images according to claim 6, wherein the large-diameter additive particles have an arithmetic mean particle size of 100 nm or more.

8. 8. The method for producing a toner for developing an electrostatic image according to claim 6, wherein in the toner mixed in the mixing step, a free ratio representing a ratio of the additive particles not adhering to the toner particles is 60% or less, and a strong adhesion ratio representing a ratio of the additive particles adhering to the toner after ultrasonic desorption treatment is 30% or less for the large-diameter external additive and 80% or less for the small-diameter external additive.

9. The method for producing a toner for developing an electrostatic image according to claim 1 , wherein the additive particles contain inorganic oxide particles.

10. 10. The method for producing a toner for developing electrostatic images according to claim 9, wherein the inorganic oxide particles contain large-diameter inorganic oxide particles having an arithmetic mean particle size of 60 nm or more and small-diameter inorganic oxide particles having an arithmetic mean particle size of less than 60 nm.

11. The method for producing a toner for developing an electrostatic image according to any one of claims 1 to 10, wherein a mixing time in the mixing step is from 5 minutes to 30 minutes.

12. A method for producing a toner for developing an electrostatic image according to any one of claims 1 to 11, wherein the agitator blade is a combination of an upper blade and a lower blade.

13. The additive particles include one or more types of large-diameter additive particles having an arithmetic mean particle size of 60 nm or more and one or more types of small-diameter additive particles having an arithmetic mean particle size of less than 60 nm, 13. The method for producing a toner for developing an electrostatic image according to claim 1, wherein in the obtained toner, a strong adhesion rate representing a ratio of additive particles adhering to the toner after ultrasonic desorption treatment is 30% or less for the large diameter additive particles and 25% or more and 60% or less for the small diameter additive particles.

Citation Information

Patent Citations

  • Method of manufacturing electrophotographic toner

    JP2010224159A

  • Electrophotographic toner, developer using toner, and image forming method

    JP2013156470A

  • Production method of toner

    JP2015135486A

  • Two-component developer for electrostatic latent image development

    JP2019138987A

  • toner

    JP2020109506A